(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The Automated Writing Evaluation System (AWES) has brought convenience and vitality to writing teaching, providing a platform for students to practice independently. Research has shown that AWES can effectively develop revision abilities, improve the language level and relevance of writing. However, teachers should still combine online exercises with offline classes to maximize its effectiveness.